Salmonella enterica Serovars Enteritidis Infection Alters the Indigenous Microbiota Diversity in Young Layer Chicks - Mon, Khin K. Z.; Saelao, Perot; Halstead, Michelle M.; Chanthavixay, Ganrea; Chang, Huai-Chen; Garas, Lydia; Maga, Elizabeth A.; Zhou, Huaijun (Frontiers in Veterinary Science, 2015)
Avian gastrointestinal tracts are highly populated with a diverse array of microorganisms that share a symbiotic relationship with their hosts and contribute to the overall health and disease state of the intestinal tract. The microbiome of the young chick is easily prone to alteration in its composition by both exogenous and endogenous factors especially during the early post-hatch period. The genetic background of the host and exposure to pathogens can impact the diversity of the microbial profile that consequently contributes to the disease progression in the host. The objective of this study was to profile the composition and structure of the gut microbiota in young chickens from two genetically distinct highly inbred lines. Furthermore, the effect of the Salmonella Enteritidis infection on altering the composition makeup of the chicken microbiome was evaluated through the 16S rRNA gene sequencing analysis. One-day-old layer chicks were challenged with S. Enteritidis and the host cecal microbiota profile as well as the degree of susceptibility to Salmonella infection was examined at 2 and 7 days post-infection. Our result indicated that host genotype had a limited effect on resistance to S. Enteritidis infection. Alpha diversity, beta diversity, and overall microbiota composition were analyzed for four factors: host genotype, age, treatment, and post-infection time-points. S. Enteritidis infection in young chicks was found to significantly reduce the overall diversity of the microbiota population with expansion of Enterobacteriaceae family. These changes indicated that Salmonella colonization in the gastrointestinal tract of the chickens has a direct effect on altering the natural development of the gastrointestinal microbiota. The impact of S. Enteritidis infection on microbial communities was also more substantial in late stage of infection. Significant inverse correlation between Enterobacteriaceae and Lachnospiraceae family in both non-infected and infected groups, suggested possible antagonistic interaction between members of these two taxa, which could potentially influences the overall microbial population in the gut. Our results also revealed that genetic difference between two lines had minimal effect on the establishment of microbiota population. Overall, this study provided preliminary insights into the contributing role of S. Enteritidis in influencing the overall makeup of chicken's gut microbiota.